Respuesta :
If you would like to solve 1/(x + 3) = (x + 10)/(x - 2), you can do this using the following steps:
1/(x + 3) = (x + 10)/(x - 2)
1 * (x - 2) = (x + 10) * (x + 3)
x - 2 = x^2 + 3x + 10x + 30
0 = x^2 + 13x + 30 - x + 2
0 = x^2 + 12x + 32
0 = (x + 8) * (x + 4)
1. x = -8
2. x = -4
The correct result would be x = -8 and x = -4.
1/(x + 3) = (x + 10)/(x - 2)
1 * (x - 2) = (x + 10) * (x + 3)
x - 2 = x^2 + 3x + 10x + 30
0 = x^2 + 13x + 30 - x + 2
0 = x^2 + 12x + 32
0 = (x + 8) * (x + 4)
1. x = -8
2. x = -4
The correct result would be x = -8 and x = -4.
The solution of 1/(x + 3) = (x + 10)/(x - 2) form least to greatest are x = -8 and x = -4
How to find variables in an equation?
1/(x + 3) = (x + 10)/(x - 2)
The unknown variable is x .
Therefore,
1/(x + 3) = (x + 10)/(x - 2)
cross multiply
x - 2 = (x + 3)(x + 10)
x - 2 = x² + 10x + 3x + 30
x² + 10x + 3x - x + 30 + 2 = 0
x² + 12x + 32 = 0
x² + 4x + 8x + 32 = 0
x(x + 4) + 8(x +4)=0
(x + 4)(x + 8) = 0
Therefore,
x = -8 and x = -4
learn more on variables here: https://brainly.com/question/12214617
#SPJ5